Biomonitoring of Polycyclic Aromatic Hydrocarbon Deposition in Greenland Using Historical Moss Herbarium Specimens Shows a Decrease in Pollution During the 20th Century - Martinez-Swatson, Karen; Mihály, Eszter; Lange, Christian; Ernst, Madeleine; Dela Cruz, Majbrit; Price, Michelle J.; Mikkelsen, Teis Nørgaard; Christensen, Jan H.; Lundholm, Nina; Rønsted, Nina (Frontiers in Plant Science, 2020)
Although most point sources of persistent organic pollutants (POPs), including polycyclic aromatic hydrocarbons (PAHs), are at lower latitudes, the Arctic region is contaminated. In particular, PAHs now dominate the POP body burden of the region’s marine biota at the lower trophic levels. Greenlandic Inuits have the most elevated levels of POPs in their blood compared to any other population, due to their consumption of seal meat and other marine mammals. PAHs, the by-products of the incomplete combustion of petroleum products, are known carcinogens and have been shown to affect the immune system, reproduction, endocrine functions, and the nervous system. With industrial activities and climate change set to increase local PAH emissions, it is paramount to document changes in atmospheric PAH deposition to further investigate PAH exposure in the region and attribute contaminations to their sources. As a measure of atmospheric pollution, we sampled bryophyte herbarium specimens of three common and widespread species collected in Greenland between the 1920s and 1970s after which time new collections were not available. They were analyzed for 19 PAHs using GC-MS (gas chromatography mass spectrometry). The presence of more low-molecular-weight PAHs than high-molecular-weight PAHs is evidence that the PAH contamination in Greenland is due to long-range transport rather than originating from local sources. The results show peaks in PAH atmospheric deposition in the first part of the 19th century followed by a trend of decrease, which mirror global trends in atmospheric pollution known from those periods. PAHs associated with wood and fossil-fuel combustion decrease in the 1970s coinciding with the disappearance of charcoal pits and foundries in Europe and North America, and a shift away from domestic heating with wood during the 19th century. The results highlight the value of bryophytes as bioindicators to measure PAH atmospheric pollution as well as the unrealized potential of herbaria as historical records of environmental change.